PENYELENGGARAAN ELEARNING MENGGUNAKAN WIZIQ DALAM PEMBELAJARAN PARENTING PADA KOMUNITAS INSTITUT IBU PROFESIONAL - Indah Purwandini (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
Education is one important factor for the progress of the nation and the State. Education is one of the efforts to improve the quality of human resources. Family education takes the role of parents as primary educators. Mother became the main foundation of family education. Mothers who are intelligent in educating children will form a family of good quality. Mother professional Institute is a community and social movement To empower women, especially mothers. One of the programs initiated by the Institut Ibu Profesional The lectures online by using WizIQ.